HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP PENCEGAHAN KANKER SERVIKS MELALUI VAKSINASI HUMAN PAPILOMA VIRUS (HPV) DI SMK PGRI 3 DENPASAR - P Novi Sagitarini (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2019)
Background: Globally, cervical cancer ranks fifth and ranks second in all cancers in women in Indonesia. One of the factors that influence the incidence of cervical cancer is the age of first sexual intercourse. About 33.3% of female adolescents started dating when they were not yet 15 years old, at that age it was feared that they did not have adequate life skills, so they were at risk of having unhealthy dating behaviors such as premarital sex. Providing information related to HPV vaccination can increase their knowledge so that it will affect how young women behave towards prevention of cervical cancer through HPV vaccination. This study aims to determine the relationship between knowledge and attitudes of young women to prevent cervical cancer through HPV vaccination. Methods: The cross sectional survey was conducted on 269 people. Data was collected in December 2016-January 2017 using questionnaire. Bivariate data analysis using Rho Spearman test to determine the relationship between knowledge and attitudes of young women to prevent cervical cancer through HPV vaccination. Results: The results showed that there was a significant relationship between knowledge and attitudes of young women towards the prevention of cervical cancer through HPV vaccination with p values <0.05 and r = 0.859. Conclusion: The attitude of young women towards the prevention of cervical cancer through HPV vaccination is related to the knowledge possessed by the teenager.Keywords: Attitude; HPV vaccination; Knowledge; Teenage girl